Peran Gereja Dalam Penanggulangan HIV/AIDS - Susanti Embong Bulan; Krispus Manullang (Journal of Religious and Socio-Cultural, 2020)
HIV (human immunodeficiency virus) is a deadly virus and there is no cure until now. The impact of the HIV / AIDS virus on a global scale, seeing this, it requires serious handling from various stakeholders, including government, parents, and even churches. Thus, the aim of this study is to provide input on the role of the church in participating in the prevention and handling of the HIV / AIDS virus. This research method uses literature study. The result of this research is that the church is obliged to participate in speaking out for danger, prevention and handling in an integrated manner with the government and other institutions. HIV (human immunodeficiency virus) adalah virus yang mematikan dan belum ada obatnya hingga saat ini. Dampak dari virus HIV/AIDS berskala global, melihat hal ini maka perlu penanganan yang serius dari pelbagai stakeholder, baik pemerintah, orang tua, bahkan gereja. Dengan demikian, tujuan dari penelitian ini adalah untuk memberikan masukan bagaimana peran gereja dalam ikut serta pencegahan dan penanganan dari virus HIV/AIDS. Metode penelitian ini menggunakan studi kepustakaan. Hasil dari penelitian ini adalah gereja wajib turut serta berpartisipasi dalam menyuarakan bahaya, pencegahan, dan penanganan secara terintegrasi dengan pemerintah dan lembaga lain.